2014
DOI: 10.1111/jen.12112
|View full text |Cite
|
Sign up to set email alerts
|

Artificial diets used in mass production of the New World screwworm, Cochliomyia hominivorax

Abstract: The New World screwworm, Cochliomyia hominivorax (Coquerel) (Diptera: Calliphoridae), has been eradicated from North and Central America using the sterile insect technique. This success has been based on mass production of high-quality screwworms using artificial diets since 1958. Many diet formulations for both larvae and adults have been developed, mainly driven by cost efficiency and material supply. However, only four larval and two adult diet formulations have been applied in the six sterile fly mass prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Our data showed that the survival time of O. arenosella larvae was significantly affected by the concentration of brewer's yeast and indicated that 4% brewer's yeast should be adopted for the artificial diet. Sucrose, or another sugar, is an indispensable ingredient in artificial diets for Lepidoptera (Hervet et al 2016), Diptera (Vanderzant 1974;Tachibana and Numata 2001;Chen et al 2014), and Coleoptera (Vanderzant 1974;Ichiki et al 2009;Tan et al 2015). In the present study, sucrose was the primary ingredient affecting the development time of larvae, pupation rate, and emergence rate of O. arenosella, similar to the results found for Ceratitis capitata (Nestel and Nemny-Lavy 2008), Drosophila melanogaster (Rovenko et al 2015), and Chilo suppressalis (Han et al 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Our data showed that the survival time of O. arenosella larvae was significantly affected by the concentration of brewer's yeast and indicated that 4% brewer's yeast should be adopted for the artificial diet. Sucrose, or another sugar, is an indispensable ingredient in artificial diets for Lepidoptera (Hervet et al 2016), Diptera (Vanderzant 1974;Tachibana and Numata 2001;Chen et al 2014), and Coleoptera (Vanderzant 1974;Ichiki et al 2009;Tan et al 2015). In the present study, sucrose was the primary ingredient affecting the development time of larvae, pupation rate, and emergence rate of O. arenosella, similar to the results found for Ceratitis capitata (Nestel and Nemny-Lavy 2008), Drosophila melanogaster (Rovenko et al 2015), and Chilo suppressalis (Han et al 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Of the two All-in-one lines made, 7# would appear to be more promising for mass rearing as this line produced more pupae from 1000 eggs on diet supplemented with tetracycline. Pupal production per gram of eggs is one of the most important biological parameters in the C. hominivorax mass rearing facility 21 . In addition, it will be necessary to determine if other important fitness parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve very high levels of tTA expression it was necessary to employ a core promoter for a L. cuprina hsp70 gene 20 . While the TSSs produced only males, female lethality was at the late larval/pupal stages, which is too late a stage for any appreciable savings in diet costs in a mass-rearing facility 21 .…”
mentioning
confidence: 99%
“…However, at lower levels of 10 and 3 μg/mL tetracycline, female viability decreased significantly ( P  < 0.01), with few females surviving on diet with 3 μg/mL tetracycline. An alternative larval diet for screwworms is based on soy protein instead of fishmeal protein, which has the benefit of being more reproducible from batch to batch, more economic, and easier to obtain [15]. A tetracycline dose response assay is presented also for soy meal diet with similar results, observing a significant decrease in female viability on diet that contained tetracycline at 0, 3, or 10 μg/mL ( P  < 0.01) (Additional file 3B).
Fig.
…”
Section: Resultsmentioning
confidence: 99%